Development of parameters of traffic sign management system in India - Kumar, Samresh; sharma, Devendra; Mahla, Rahul (International Journal of Computer Sciences and Engineering, 2025)
Asset management is a systematic process of maintaining, upgrading and operating assets. Road asset management is focused on bridges, traffic signs, pavement markings, culverts. This paper focuses on the development of traffic sign asset management system. For this we have to conduct a visual night time inspection method to find the Retro-reflectivity of a sign. This survey will be conducted at regular night time intervals. This survey will be conducted at minimum vehicle distances with vehicle high beam lights. And some of traffic signs should be failed the test they should not visible to the driver. And some signs need for maintenance. In the management study, we have to take manufacture cost of each sign and maintenance cost of the signs. For this we need to replace the some signs and maintenance should be required for some signs. And should note the latitude and longitude of the sign and create a file in the arc GIS and should plot a position of the each sign.